Racismo no contexto da saúde: um estudo psicossociológico - Miranda, Rosane de Sousa (2015)
Over the years has being forged in Brazil, belief that this is a mixed nation, living with their diversity in perfect harmony in a racial democracy. However, when penetrate into race relations established in daily life and in institutions can be perceived disparities and inequalities, where minority groups are sidelined. Given these assumptions, the aim of this thesis is investigate racism in health care from users perception. To realize it was necessary to carry out two empirical studies. In the first study was done the adaptation and validation of Racial Discrimination Perception Scale Health - Versions Personnel and General. Locus Search: great João Pessoa. Participants: 214 adults. Instruments: Survey Biosociodemographic; Scale Perception of Racial Discrimination in Health - Personal version (EPDRS-VP); Scale Perception of Racial Discrimination in Health - General Version (EPDRS-VG). Analysis: descriptive statistics and measures of central tendency and dispersion and also those bivariate and multivariate like Exploratory Factor Analysis, Cronbach's alpha and MANOVA. Results: Both EPDRS-VP as the EPDRS VG-factor structure and had adequate internal consistency, α = 0.94 and α = 0.93, respectively, presenting appropriate psychometric standards. Seeking to understand racism in health context in many aspects, then proceeded to the second investigation, the validated scales were used as one of variables to investigate the social representations forged by the participants on the theme. Locus Search: João Pessoa. Participants: 30 adults. Criteria for inclusion in sample: (i) be more than 18 years; (ii) accept participate in the study, and (iii) be user of health services. Instruments: Free Association Test (FAT) with stimuli: health, racism, racism in health, health care and SUS; Biosociodemographic questionnaire; EPDRS-VP; EPDRS-VG. Analysis: the biosociodemographic questionnaire was submitted to descriptive and inferential statistics; The scales were analyzed using descriptive and inferential statistics. The data from the TALP underwent factorial correspondence analysis. The semi-structured interviews was analyzed using lexical analysis of content. Results: The analysis of social representations highlighted the polarization of speech around the affirmation/denial of racism in health context. Social insertion in activities related to racial issue and racial discrimination were perceived characteristic of speech that affirms the existence of racism in health, while the denial was linked to catholicism, white people and low perception of racial discrimination. The findings highlight the relevance to discuss racism in the health context. It is expected that the results may shed light on the existence of racism in health services and collaborate with actions related to the National Policy for Integral Attention to Health of the Black Population.